1995
DOI: 10.1007/bf00231067
|View full text |Cite
|
Sign up to set email alerts
|

Adaptational and learning processes during human split-belt locomotion: interaction between central mechanisms and afferent input

Abstract: Split-belt locomotion (i.e., walking with unequal leg speeds) requires a rapid adaptation of biomechanical parameters and therefore of leg muscle electromyographic (EMG) activity. This adaptational process during the first strides of asymmetric gait as well as learning effects induced by repetition were studied in 11 healthy volunteers. Subjects were switched from slow (0.5 m/s) symmetric gait to split-belt locomotion with speeds of 0.5 m/s and 1.5 m/s, respectively. All subjects were observed to adapt in a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
87
3
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 124 publications
(102 citation statements)
references
References 23 publications
11
87
3
1
Order By: Relevance
“…This pattern is based on the organisation of the central pattern generator. The responses to the single joint displacements applied here were similar in their organisation to those seen during unilateral whole limb perturbations during gait in adults (Dietz et al 1987;Ghori and Luckwill 1989;Prokop et al 1995; for review see Dietz 1992) and infants (Pang andYang 2000, 2001). However, in the present study, the strength of bilateral leg muscle activation depended on the direction of the displacement.…”
Section: Bilateral Co-ordinationmentioning
confidence: 52%
“…This pattern is based on the organisation of the central pattern generator. The responses to the single joint displacements applied here were similar in their organisation to those seen during unilateral whole limb perturbations during gait in adults (Dietz et al 1987;Ghori and Luckwill 1989;Prokop et al 1995; for review see Dietz 1992) and infants (Pang andYang 2000, 2001). However, in the present study, the strength of bilateral leg muscle activation depended on the direction of the displacement.…”
Section: Bilateral Co-ordinationmentioning
confidence: 52%
“…This type of flexible coordination has been reported for many animal preparations, including stick insects (Foth and Bassler, 1985), spinal (Forssberg et al, 1980), decerebrate (Kulagin and Shik, 1970) and intact cats (Halbertsma, 1983), and spinal turtles (Stein and McCullough, 1998). Split-belt studies in human adults showed some independence of the pattern generators for each leg in relation to learning (Prokop et al, 1995), but asymmetrical stepping has not been reported. We confirm here that the putative human infant pattern generator for each limb shows some autonomy much like that in other animals.…”
Section: Independence Of the Pattern Generator For Each Limbmentioning
confidence: 60%
“…All previous reports of human adults stepping on split-belt treadmills have reported alternate stepping, with left and right steps alternating in a 1:1 manner (Dietz et al, 1994;Prokop et al, 1995;Jensen et al, 1998). No asymmetrical stepping rhythms were reported.…”
Section: Introductionmentioning
confidence: 85%
“…This alternative hypothesis is supported by studies showing subjects are remarkably adept at predicting the overall timing of locomotion associated with regularly paced steps using motor imagery (Bakker et al 2007;Decety et al 1989;Papaxanthis et al 2002a). Thus the strength of the grip-inertial force coupling may be determined by the regularity of the walking cycle in a manner similar to the coordination of breathing with walking, running, or other cyclical limb movements (i.e., via entrainment) (Bernasconi et al 1995;Ebert et al 2000;Kohl et al 1981;Rassler and Kohl 2000;Seebauer et al 2003), and a shift from a regular pattern to an irregular one could disrupt this relationship (e.g., Nishino and Hiraga 1991;Prokop et al 1995;Reisman et al 2005).…”
Section: Introductionmentioning
confidence: 99%